Hierarchical method using ethnographic data sets to guide archaeological research: Testing models of plant intensification and maize use in Central Western Argentina - Johnson, Amber (2015)
Ethnographic and environmental data sets developed by Lewis Binford are used to test models about the relationship between forager plant intensification and maize adoption in Central Western Argentina. By examining large suites of cases to identify regular patterns of association, the models describe regular interactions that are apparent in the patterning across known groups. To the extent that people in the past adapted in similar ways to environmental and demographic conditions as people recorded ethnographically, they may be expected to fall within the bounds of general ecological relationships.